METHODOLOGICAL PRE-CONDITIONS OF COMPETENCE APPROACH FORMING IN THE USA AND EUROPEAN - Iryna V. Sekret (Інформаційні технології і засоби навчання, 2010)
According to the demands of the Bologna convention and under the circumstances of the national education transformation the competence approach to the specialist’ training is of special concern. In this connection main characteristics of the competence approach are under the view. The terms “competence” and “competency” in their different references are studied. Besides the article deals with main trends of the competence approach development in USA and European countries.